FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL - Mirna Wati; Anita Wijayanti; Purnama Siddi (Universitas Muria Kudus, 2020)
Capital structure is the ratio between debt (foreign capital) and own capital (equity). There are several factors that affect capital structure such as dividend policy, liquidity, tangibility, asset turnover and company growth. This study aims to determine the effect of dividend policy, liquidity, tangibility, asset turnover and company growth on capital structure. In this study, the sampling method was carried out using purposive sampling and obtained as many as 14 companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange during 2015-2018. Thus the amount of data observed in this study amounted to 56 data. Data in this study were analyzed using Statistical Package for Social Sciences (SPSS) 22 with multiple linear regression analysis methods. The results of this study indicate that liquidity and asset turnover affect the capital structure while the dividend policy, tangibility and company growth do not affect the capital structure.